Air – conditioners as source of Infection - Uppal, Taj B. (Journal of Postgraduate Medical Institute, 2011)
Condensation water from 15 air-conditioners, fixed in different kinds of room, was tested a regards their bacterial contents. Bacillus spp. was also found in almost all the water tested but Pseudomonas aeruginosa was also found from air-conditioners fixed in rooms with heavy traffic. Proper disposal of this water, especially in hospitals, is recommended as it may become a source of infection to any susceptible person.